2011
DOI: 10.1016/j.jvs.2010.07.064
|View full text |Cite
|
Sign up to set email alerts
|

Standardization is superior to traditional methods of teaching open vascular simulation

Abstract: This study demonstrates the feasibility of open vascular simulation to assess the effect of differing teaching methods on performance outcome. Findings from this report suggest that for simulation training, standardized may be more effective than traditional methods of teaching. Transferability of simulator-acquired skills to the clinical setting will be required before open simulation can be unequivocally recommended as a major component of resident technical skill training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…[7][8][9][10][11] Although the effectiveness of simulation training has not been as widely investigated in open vascular surgery as it has in other surgical disciplines, evidence for its benefit is emerging. 5,[12][13][14] The Association of Program Directors in Surgery in conjunction with the American College of Surgeons has outlined a surgical skills curriculum for general surgery residents. 15,16 The Residency Review Committee in Surgery has mandated the use of surgical skills laboratory training for surgical residents.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] Although the effectiveness of simulation training has not been as widely investigated in open vascular surgery as it has in other surgical disciplines, evidence for its benefit is emerging. 5,[12][13][14] The Association of Program Directors in Surgery in conjunction with the American College of Surgeons has outlined a surgical skills curriculum for general surgery residents. 15,16 The Residency Review Committee in Surgery has mandated the use of surgical skills laboratory training for surgical residents.…”
mentioning
confidence: 99%
“…Regarding the training method, 1 study revealed that standardization (where 1 instructor taught the same procedure repeatedly) was more effective than traditional training (where different surgeons supervise simulation training). 23 Another study demonstrated that AAA-specific simulation training was effective for improving surgical skills. 8 However, these studies were limited by the relationship between simulation training and the outcomes of practical OS, which comprises complex procedures, not being clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical residents who were randomized to the standardized approach developed better technical skills, motion efficiency, and accuracy. Furthermore, in a post-study evaluation, more than 70% of surgical residents reported a preference for a standardized training approach [10]. In addition, use of the penoscrotal approach has been shown to decrease risk of dorsal nerve injury, improve the surgeon's ability to anchor the pump in the scrotum, and improve corporeal exposure [11].…”
Section: Discussionmentioning
confidence: 99%